Virulence Factors in Coagulase-Negative Staphylococci - Angela França; Vânia Gaio; Nathalie Lopes; Luís D. R. Melo (Pathogens, 2021)
Coagulase-negative staphylococci (CoNS) have emerged as major pathogens in healthcare-associated facilities, being S. epidermidis, S. haemolyticus and, more recently, S. lugdunensis, the most clinically relevant species. Despite being less virulent than the well-studied pathogen S. aureus, the number of CoNS strains sequenced is constantly increasing and, with that, the number of virulence factors identified in those strains. In this regard, biofilm formation is considered the most important. Besides virulence factors, the presence of several antibiotic-resistance genes identified in CoNS is worrisome and makes treatment very challenging. In this review, we analyzed the different aspects involved in CoNS virulence and their impact on health and food.